2012
DOI: 10.1021/jf204556u
|View full text |Cite
|
Sign up to set email alerts
|

A Protease-Insensitive Feruloyl Esterase from China Holstein Cow Rumen Metagenomic Library: Expression, Characterization, and Utilization in Ferulic Acid Release from Wheat Straw

Abstract: A metagenomic library of China Holstein cow rumen microbes was constructed and screened for novel gene cluster. A novel feruloyl esterase (FAE) gene was identified with a length of 789 bp and encoded a protein displaying 56% identity to known esterase sequences. The gene was functionally expressed in Escherichia coli BL21 (DE3), and the total molecular weight of the recombined protein was 32.4 kDa. The purified enzyme showed a broad specificity against the four methyl esters of hydroxycinnamic acids and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The total length of the CDS was 13,050,867 bp, accounting for 42.74% of the total genome length. Furthermore, 47 rRNAs (2 and 45 copies of 28S and 5S rRNAs, respectively) and 191 tRNAs were identified by rRNAmmer (Version 1.2) and tRNAscan-SE (Version 1.3.1), respectively [12,13].…”
Section: Genome Features and Gene Function Analysis Of Strain M1816mentioning
confidence: 99%
See 2 more Smart Citations
“…The total length of the CDS was 13,050,867 bp, accounting for 42.74% of the total genome length. Furthermore, 47 rRNAs (2 and 45 copies of 28S and 5S rRNAs, respectively) and 191 tRNAs were identified by rRNAmmer (Version 1.2) and tRNAscan-SE (Version 1.3.1), respectively [12,13].…”
Section: Genome Features and Gene Function Analysis Of Strain M1816mentioning
confidence: 99%
“…This shows that we have screened a strain with good enzyme production performance. In addition, many studies have reported that only low levels, or no detectable levels, of free FA were released from wheat by FAE, cellulase, β-1,3-glucanase, and β-1,4-endoxylanase [13,47]. Many studies have shown that the synergy of multiple enzymes can significantly increase the release of FA [60,61].…”
Section: Release Of Fa From Dswbmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al (74) screened for feruloyl esterase activity in a metagenomic library obtained from the microbial population of a cow rumen and identified a protease-resistant feruloyl esterase, which can release ferulic acid from wheat straw. This particular esterase has great commercial application because of its high pH and thermal stability and protease resistance.…”
Section: Esterasesmentioning
confidence: 99%
“…They have a dual usefulness as they not only break down plant biomass (which is useful in industrial waste management) but, in doing so, they de-esterify dietary fibers releasing bioactives with potential beneficial health effects (reviewed by Faulds, 2010 ). In a study carried out by Cheng et al ( 2012a ), a metagenomic library constructed from the microbial content of a Chinese Holstein cow rumen was functionally screened for feruloyl esterase activity, identifying a protease-insensitive feruloyl esterase capable of releasing FA from wheat straw. This novel enzyme is of particular industrial interest as it showed high thermal and pH stability and was resistant to several proteases including pepsin.…”
Section: Applications Of Interest Of Functional Metagenomics In Food mentioning
confidence: 99%